If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -21 = 3x + -12 Reorder the terms: -21 + 6x = 3x + -12 Reorder the terms: -21 + 6x = -12 + 3x Solving -21 + 6x = -12 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -21 + 6x + -3x = -12 + 3x + -3x Combine like terms: 6x + -3x = 3x -21 + 3x = -12 + 3x + -3x Combine like terms: 3x + -3x = 0 -21 + 3x = -12 + 0 -21 + 3x = -12 Add '21' to each side of the equation. -21 + 21 + 3x = -12 + 21 Combine like terms: -21 + 21 = 0 0 + 3x = -12 + 21 3x = -12 + 21 Combine like terms: -12 + 21 = 9 3x = 9 Divide each side by '3'. x = 3 Simplifying x = 3
| -16(4a-9b+2c)= | | (14/3)x=-126/11 | | 4(n+4)=-2+7n | | 4.2x+4=25 | | 5(x)X(25)2x=5 | | (957/14)x=18 | | 2(3x+5)+2(8x-7)=180 | | 112x5/14 | | (22/3)x=7 | | 5x-2=41 | | 9e^4x=196 | | 5g+3.29=25.24 | | .069x+x=20 | | 4.905x*x=11 | | 127+x+(x-10)+(x-3)=180 | | .06x-2=3+0.4x | | -48+11n-20n+12=0 | | 6a+18-10=-2a-8 | | -45=-(1+2n)-6+(4-2n) | | -8(6-8b)+3(1+6b)=37 | | 8y-6=34 | | xsquared+21x+20= | | x+21x+20= | | 127+x+(x-10)+(x-3)=360 | | 293+(2x-5)+x=360 | | 5=1/1-0.25*(1-x) | | 5x-2x=-28 | | 2a+3b+1-6b+a+5= | | X-.15x=62 | | (5x-13)+(2x)+(4x+13)+x=360 | | 12-2(4+4x)=-8x+4 | | 4=1/1-0.8*(1-x) |